2016
DOI: 10.3390/nu8110667
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary Behavior Is Independently Related to Fat Mass among Children and Adolescents in South China

Abstract: We aim to explore the independent associations of sedentary behaviors (SB) with body mass distribution among Chinese children. Data on the screen-based sedentary time (television viewing and computer use) and doing homework, physical activities and dietary intake of 1586 Chinese children (50.3% girls) aged 7–15 years were obtained through validated questionnaires. Skin-fold thickness, body height, and weight were measured to calculate percent body fat (%BF), fat mass index (FMI), and fat-free mass index (FFMI)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…This epidemiological and nutritional picture is explained, in large part, by the changes that have been occurring in the food pattern, resulting in more and more common obesogenic diets 2 . Add to this the reduction of physical activity and an increase in the practice of sedentary activities, such as watching television 3 . In addition, other factors associated with the etiology of obesity in children are: parental obesity, maternal diabetes, maternal smoking, gestational weight gain 4 , inadequate sleep 5 , influences of the family and school environment 6 , socioeconomic and educational aspects of the family 7 , among others.…”
Section: Introductionmentioning
confidence: 99%
“…This epidemiological and nutritional picture is explained, in large part, by the changes that have been occurring in the food pattern, resulting in more and more common obesogenic diets 2 . Add to this the reduction of physical activity and an increase in the practice of sedentary activities, such as watching television 3 . In addition, other factors associated with the etiology of obesity in children are: parental obesity, maternal diabetes, maternal smoking, gestational weight gain 4 , inadequate sleep 5 , influences of the family and school environment 6 , socioeconomic and educational aspects of the family 7 , among others.…”
Section: Introductionmentioning
confidence: 99%
“…Body fat is a normal component of human body that accumulates in adipose tissue. It serves as a useful marker for assessing adiposity of individuals (Hu 2008;Sen and Mondal 2013;Colley et al 2015;Griffiths et al 2016;Xue et al 2016). The predictions of body fatness and body composition are based most-ly upon anthropometric measures such as height, weight, percentage body fat (PBF), body mass index (BMI), waisthip ratio and skinfold thickness (Rolland-Cachera 1993;Hall et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…BMI can be better expressed in terms of fat mass (FM) and fat free mass (FFM) [BMI = FFM (kg)/height 2 (m 2 ) + FM (kg)/height 2 (m 2 )] (Wells 2010) and it also includes the FM index (FMI) and FFM index (FFMI). The disintegration of BMI into FM and FFM needs the help of anthropometric measurements and body composition assessment (VanItallie et al 1990;Wells 2010;Sen and Mondal 2013;Xue et al 2016;Sharma and Mondal 2018). Body composition status reflects nutritional intakes, losses and needs over time (i.e., FFM and FFMI) along with the prevalence of undernutrition.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review found moderate evidence for the association between television viewing and overweight in preschoolers (Te Velde et al 2012). One study in China indicated that sedentary behaviors might be positively and independently related to fat mass among Chinese children (Xue et al 2016). While the crosssectional nature of this study does not allow for any conclusions vis-àvis cause and effect, our findings are consistent with the hypothesis that ST or LPA constitutes a major contributing factor in the development and continuation of childhood obesity (Trost et al 2003).…”
Section: Discussionmentioning
confidence: 99%